Interjurisdictional competition for higher education and firms - Marcel Gérard; Fernando M. M. Ruiz (Center for Economic Studies and ifo Institute (CESifo), 2006)
In this paper we consider two regions competing for the larger part of the investment by a mobile firm whose decision is based on the quality of human capital in each region. This in turn depends on the initial skill level and the amount of higher education in the region, with a possible spillover to the other region. Therefore each region, through subsidies, tries to attract a larger part of the academic community. Moreover a central government or agency helps the poorer region by providing it with an extra budgetary allocation. The game is nested in a series of settings which are compared, especially from the point of view of their redistributive efficiency. From a policy point of view, the paper, in line with the subsidiarity principle, first provides an argument for allocating a significant amount of the competence in matters of human capital formation, to the central authorities. It also set forth difficulties which can arise from centralizing such an amount of competence and pleas for clear rules governing the federation, especially ruling out discretionary and opportunistic behaviors of public authorities. Finally, it shows the importance of the central government being correctly informed, including being allowed to gather information by itself.
Keywords: H41; H77; I20; 330